Design of microstrip patch antenna at S-band frequency for satellite communication / Noor Aida Mohd Yusoff - Mohd Yusoff, Noor Aida (2015)
This paper consists of a design of microstrip patch antenna at S-band for satellite communication. This antenna designed to operate at S-band frequency which is at 2.4 GHz using Computer Simulation Technology (CST) software. The antenna designs were started with a basic microstrip patch antenna and proceed with power divider and to design an antenna array. Combination of microstrip patch antenna and power divider called antenna array. The return loss (Sn) result for antenna array is -18.89dB and 1.22 for voltage standing wave ratio (VSWR).